2009
DOI: 10.1094/phyto-99-11-1273
|View full text |Cite
|
Sign up to set email alerts
|

Development of a TaqMan Real-Time PCR Assay for Quantification of Airborne Conidia of Botrytis squamosa and Management of Botrytis Leaf Blight of Onion

Abstract: The use of a DNA-based method for quantifying airborne inoculum of Botrytis squamosa, a damaging pathogen of onion, was investigated. A method for purifying DNA from conidia collected using rotating-arm samplers and quantifying it using a TaqMan real-time quantitative polymerase chain reaction (qPCR) assay is described. The sensitivity of the qPCR assay was high, with a detection limit of 2 conidia/rod. A linear relationship between numbers of conidia counted with a compound microscope and those determined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 37 publications
(56 reference statements)
0
53
0
Order By: Relevance
“…However, qPCR has been also used to quantify the airborne inoculum of fungal pathogens, such as Sclerotinia sclerotiorum, Leptosphaeria spp., Puccinia striiformis, and Botrytis squamosa (38,39,40,41), which cause serious disease in arable crops, and also for the forest tree pathogen Fusarium circinatum (20,42). Many fungal diseases are initiated by airborne inoculum that lands on susceptible hosts under favorable environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, qPCR has been also used to quantify the airborne inoculum of fungal pathogens, such as Sclerotinia sclerotiorum, Leptosphaeria spp., Puccinia striiformis, and Botrytis squamosa (38,39,40,41), which cause serious disease in arable crops, and also for the forest tree pathogen Fusarium circinatum (20,42). Many fungal diseases are initiated by airborne inoculum that lands on susceptible hosts under favorable environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…At the damage thresholds of five or ten lesions/leaf, conidia quantification with qPCR assay was more reliable at predicting disease risk than by microscopical counting of conidia. The results indicated that the qPCR protocol was reliable for quantifying B. squamosa airborne inoculum in commercial onion fields, providing a dependable basis for disease risk assessment (Carrise et al 2009). …”
Section: Detection Of Fungal Pathogens In Airmentioning
confidence: 96%
“…Spore sampling protocols were implemented for P. viticola sporangia (Kast, 1997) and E. necator conidia (Carisse et al, 2009a). Spore sampling was greatly improved by the use of molecular tools in order to speed up the counting process, as proposed by Carisse et al (2009b) to develop real-time quantification of the airborne conidia of B. cinerea.…”
Section: Scoutingmentioning
confidence: 99%